Development of a Holistic Pre-Marital Assistance ModuleNon-Counseling for Prospective Bride and Groom Couples at the KUA Bungursari District, Purwakarta Regency 2026 - Dwi Widyastuti; Eka prihatin; Anitasari (International Journal of Health and Pharmaceutical (IJHP), 2026)
Marriage is a fundamental social institution that determines the quality of family resilience and human resource development. Premarital preparedness is a key factor in preventing marital conflict, domestic violence, and divorce. A preventative approach through premarital education is a crucial strategy for strengthening family resilience. Globally, the WHO emphasizes the importance of education-based promotive and preventive approaches to improve individual readiness to enter family roles, especially in the productive age group. In Purwakarta, the phenomenon of early marriage and the social dynamics of urban-rural transition communities demonstrate the need for education-based preventive interventions. The current approach is still dominated by couples counseling, while individual empowerment—especially for prospective brides and grooms, both men and women, before marriage has not been systematically developed in the form of structured modules. Therefore, innovation is needed in the form of developing a non-counseling holistic pre-marital assistance module for prospective brides and grooms that is oriented towards preventive education and strengthening self-capacity. The holistic approach in this study includes the following dimensions: psychological and emotional readiness, social maturity and communication, financial literacy and economic responsibility, reproductive and mental health, spiritual values ​​and family leadership. This research was conducted as a preliminary study in the Purwakarta area, the compiler chose the Bungursari area because of its large population coverage, based on KUA data in 2026 it was stated that in the last 3 months in October there were 28 couples of brides and grooms, November 29 couples of brides and grooms, December 11 couples of brides and grooms, January 30 couples of brides and grooms, so the compiler chose to take total sampling data as research material for 30 couples of brides and grooms for the period. January 2026